Limited evidence exists on the effectiveness of education and training interventions on trial recruitment; a systematic review - Cronin, Patricia; Hennessy, Martina (My University, 2019)
Objective: The objective of this study was to examine the effectiveness of education and training interventions on recruitment to randomized and non-randomized trials. Study design and setting: A systematic review of the effectiveness of education and training interventions for recruiters to trials. The review included randomized and non-randomized controlled trials of any type of education and training intervention for recruiters to trials, within any health care field. The primary outcome was recruitment rates, and secondary outcomes were quality of informed consent, recruiter self-confidence, understanding/knowledge of trial information, numbers of potential trial participants approached, satisfaction with training, and retention rates. Results: Of the 19 records reviewed at full-text level, six met the inclusion criteria for our review. Owing to heterogeneity of outcomes and methods between the included studies, meta-analysis was not possible for the primary outcome. Of the three studies that reported recruitment rates, one favored the education and training intervention for increased recruitment; the remaining two found no differences between the groups. Of the reported secondary outcomes, quality of informed consent was improved, but no differences between groups in understanding/knowledge of trial information were found. Conclusion: There is limited evidence of effectiveness on the impact of education and training interventions on trial recruitment. Further work on developing a substantial evidence base around the effectiveness of education and training interventions for recruiters to trials is required.
PUBLISHED
Keywords: Trial methodology; Educational intervention; Effectiveness review; Systematic review; Training intervention; Trial recruitment; International Integration